EMPOWERING FOREST BATHING TOUR GUIDES FOR YOGURT PRODUCTION IN LEREP UNGARAN BARAT VILLAGE, SEMARANG REGENCY - Susilorini, Susilorini; Yuniarifa, Conita; Hussaana, Atina; Riza, Mohamad (LPPM Univ. Ibn Khaldun Bogor, 2024)
Wellness tourism is a tourist activity that not only aims for entertainment and pleasure, but also health. Lerep Village is one of the tourist villages that has a lot of potential to be developed into one of the wellness tourism objects. One of the highlights is the culinary sold in the traditional Sunday Pon market based on local wisdom. Currently there is no development of yogurt-based products in this traditional market, even though there is a lot of potential from livestock and agricultural products that can be developed as yogurt products. Yogurt is one type of food rich in bacteria which is expected to be one way to maintain public health, especially digestive health. Tourism cadres in this village have long been fostered by the Faculty of Medicine of Sultan Agung Islamic University, especially in the development of forest bathing tourism. This service activity aims to provide basic education and training to 20 forest bathing tourism cadres in traditional yogurt making. The training was held for 1 day with counseling methods and one-day training. Before and after the training, the participants were given pretest and post test, and the results of a significant increase in knowledge were obtained from the participants. After this training, it is hoped that the tourism cadres can produce yogurt so that it can become one of the healthy snack choices in Lerep Tourism Village.